Serum erythropoietin concentrations in symptomatic infants during the anaemia of prematurity. Issue 7 (July 1992) - Meyer, J; Sive, A; Jacobs, P
Abstract : A comparison was carried out between a series of neonates who weighed less than 1500 g at birth and received red cell transfusions for symptomatic anaemia of prematurity (group 1, n = 14) and controls of similar gestational age and weight, who remained well and were not transfused during their nursery stay (group 2, n = 10). Mean (SD) haemoglobin concentrations at birth were 163 (12) g/l and 183 (17) g/l (p = 0.004), respectively. Transfusion resulted in significantly better weight gain in six infants who had been growing poorly:mean (SE) 8.8 (2.8) g/day improved to 23.3 (2.1) g/day (p less than 0.002). Geometric mean (SD) serum immunoreactive erythropoietin (SiEp) concentrations (17.7 (1.3) U/l) for the whole group of infants were similar to those of normal adults (17.4 (4.7) U/l) despite considerably reduced haemoglobin values. There was a significant inverse correlation between haemoglobin and log SiEp concentrations in the infants requiring transfusion (r = -0.43; p less than 0.01), but this was not apparent in the untransfused babies. Moreover, at haemoglobin concentrations below 120 g/l the mean (SE) SiEp concentration of 20 (1.08) U/l in group 1 was significantly higher than in group 2 (14 (1.06) U/l; p = 0.002). These data suggest that an increased concentration of SiEp early in the course of the anaemia of prematurity helps to identify those infants who would benefit from red cell transfusions, but that clinical criteria, although ill defined, do so equally well.